POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN MENTAL ANAK SAMPAI DEWASA DI DESA SILIAN SATU KECAMATAN SILIAN RAYA KABUPATEN MINAHASA TENGGARA - Tumigolung, Eunike Debora (HOLISTIK, Journal of Social and Culture, 2024)
Parenting is a process of interaction that occurs between parents and children. The interaction that occurs will encourage parents to want the best for their children and from this desire will then form a parenting style that will be instilled and passed on by parents to their children. However, this interaction process will have a major influence on the development of the child's personality and also affect the child's mental condition until he is an adult, because this interaction process occurs from the time they are born into the world and will provide experience in personality formation when they become adults later. But not all children do negative behavior, there are also children who do positive behavior such as many children who are diligent in worship, obey parents, and have good manners and go to school to a higher level. The phenomenon of parenting like this will be a sign of caution for parents in nurturing and educating children in the mental formation of their children. The parenting style of parents in Silian Satu Village, Silian Raya District, Minahasa Tenggara Regency on children's mental formation at the age of ten years to adulthood has a significant impact such as can affect children's self-confidence levels because children who receive positive support from their parents tend to have higher self-confidence, while children who experience negative treatment or lack of support can have higher self-confidence. low. Keywords: parenting, mental, behavior